Respuesta :

Answer: 11 and -13

Step-by-step explanation:

         first you need to isolate one variable so you can later plug it into the               other equation

x+y = -2

y = -x - 2

         now, you plug this y value into the next equation for the difference that equals 24 and solve for x

x-y = 24

x - (-x-2) = 24

2x + 2 = 24

2x = 22

x = 11

         now that you have x, you can just plug it back into either original equation to get the corresponding y equation.

11 + y = -2

y = -13

proof:

11 - (-13) = 24

11 + (-13) = -2

ACCESS MORE